A Central Asian Buddhist Term: Remarks on Khotanese saña- and Tocharian B sāñ, A ṣāñ - Del Tomba, Alessandro (Indo-Iranian journal, 2021)
Abstract The Khotanese masculine substantive saña- ‘artifice, expedient, means, method’ cannot be a loanword from the Gāndhārī feminine saṃña ‘perception, idea’ (< Sanskrit saṃjñā-), as has been recently suggested. Bilingual evidence for its meaning, its metrical use, and the contexts where it occurs show unambiguously that it differs formally and semantically from the Khotanese feminine saṃñā- ‘idea, notion, perception, etc.’, the actual loanword from Gāndhārī saṃña. Since the meaning of Tocharian B sāñ, ṣāñ and A ṣāñ ‘expedient, means’ agrees with that of Khotanese saña- ‘artifice etc.’, the old view should not be abandoned that the latter is a genuine Khotanese word < Iranian *sćandi̯a- (to the root *sćand- ‘to appear, seem (good)’) and is the source of the corresponding loanwords in Tocharian.